Pd-Catalyzed Transfer Hydrogenation of Alkenes Using Tetrahydroxydiboron as the Sole Hydrogen Donor - Yaghoubi, Mahshid; Reyes, Isabella C.; Stokes, Benjamin J. (SynOpen, 2024)
Tetrahydroxydiboron-mediated catalytic transfer hydrogenations have typically involved co-additives that, like tetrahydroxydiboron itself, are H atom donors. Herein we report an alkene transfer hydrogenation method with tetrahydroxydiboron as the sole source of H atoms. The reaction uses Pd(OAc)2 as a convenient putative colloid pre-catalyst, and cyclic monoethers are competent solvents. Highly efficient alkene deuteration is demonstrated using tetradeuteroxydiboron.
Keywords: tetrahydroxydiboron; transfer hydrogenation; palladium catalysis; alkene reduction; deuterium; catalytic hydrogenation